2020
DOI: 10.3390/ani10060959
|View full text |Cite
|
Sign up to set email alerts
|

Clicker Training Accelerates Learning of Complex Behaviors but Reduces Discriminative Abilities of Yucatan Miniature Pigs

Abstract: Animal training is meant to teach specific behavioral responses to specific cues. Clicker training (CT) is a popular training method based on the use of a device that emits a sound of double-click to be associated as a first-order conditioned stimulus in contingency with positive reinforcements. After some repetitions, the clicker sound gains some incentive value and can be paired with the desired behavior. Animal trainers believed that CT can decrease training time compared to other types of training. Herein,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…On the other hand, Smith and Davis (2008) state in their study that there was no difference between clicker and the control groups in terms of learning the behaviour, but the clicker group forgot the learned behaviour later than others. Paredes-Ramos et al (2020) report that the clicker method reduces the number of repetitions required to learn to bring an object among piglets and enables faster learning. Leidinger et al (2017) states that mice trained with the clicker method learn quickly and perform all tasks successfully.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Smith and Davis (2008) state in their study that there was no difference between clicker and the control groups in terms of learning the behaviour, but the clicker group forgot the learned behaviour later than others. Paredes-Ramos et al (2020) report that the clicker method reduces the number of repetitions required to learn to bring an object among piglets and enables faster learning. Leidinger et al (2017) states that mice trained with the clicker method learn quickly and perform all tasks successfully.…”
Section: Discussionmentioning
confidence: 99%
“…To date, one study has suggested any benefit to a clicker secondary reinforcer. Paredes-Ramos et al (2020) reported that clicker-trained piglets acquired a novel behavior in significantly fewer trials than did a verbally-reinforced group. A single trainer used a 10-step shaping protocol to teach ten piglets in each group to fetch a novel object for 30 trials a day until all piglets acquired the behavior.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Pryor (2006) has suggested that only two or three pairings are needed to establish the clicker as a conditioned reinforcer. Similarly, Chiandetti et al (2016) claimed that two or three pairings were sufficient, and neither Thorn et al (2006) nor Paredes-Ramos et al (2020) paired the auditory stimulus with the primary reinforcer at all before initiating testing. While additional pairings would be expected to more strongly establish the stimulus as a secondary reinforcer ( Wike, 1966 ), our procedure was consistent with or more substantial than others in the literature, and we were constrained by the possibility of satiation in our young subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the use of clickers for training is a method of positive reinforcement where a sound of double-click, emitted from the device, is associated to a first-order conditioned stimulus. If this action is repeated enough, animals can be taught to show desired behaviors, serving as a rewarding stimulus itself [ 35 ].…”
Section: The Seven Basic Neurobiological Systems Of Behaviormentioning
confidence: 99%